PELAYANAN PUBLIK BIDANG KESEHATAN: PENERAPAN DIGITALISAI BERBASIS APLIKASI BACK UP DATA POSYANDU DI DESA DONGKO - Kiki Amalia; Mohammad Sawir; Andi Nur’aini; Henra Rasa Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Anutapura I, II, and III Integrated Health Posts (Posyandu) in Dongko Village still use a manual recording system. This creates several problems, such as long service times, long queues, and the risk of data loss. The community service activity aims to implement the digitization of application-based Posyandu services with a data backup system. Through training and mentoring, it is hoped that Posyandu cadres will be able to use the application for fast, accurate, and transparent data recording, thereby improving service quality and better serving the community. The implementation method includes initial observation, socialization, application training, implementation in routine Posyandu activities, and ongoing evaluation and mentoring. The results of the activity show significant improvements: recording times that previously took hours can be completed in minutes, queues are drastically reduced, and data is stored more securely and easily accessed in real time. Thus, the digitization of Posyandu services has proven to be an effective solution to the problems of manual recording that have been faced.